(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2023)
The implementation of regional autonomy aims to realize regional independence. A region must have regional financial capacity to create regional independence, which can be seen from the high regional original income (PAD). Efforts to realize regional independence through increasing PAD are carried out by exploring PAD sources, one of which is by exploring potential sources of regional taxes, namely property tax in rural and urban areas (PBB-P2). PBB-P2 is a tax whose revenue increases every year as a result of the development of a region. the purpose of this study is to identify the potential for PBB-P2 acceptance and recommend strategies to increase PBB-P2 revenue. The analytical method used is PBBP2 acceptance analysis and multi-criteria policy (MULTIPOL). The results of the study show that estimated potential income that must be maximized is IDR 8.03 billion. Alternative strategies to increase PBB-P2 revenue in West Bangka Regency are through data updating policies, developing human resources, using technology, increasing the understanding and knowledge of taxpayers, and increasing supervision